Association between meteorological factors and audiogram configurations in patients with sudden sensorineural hearing loss: a cross-sectional study - Xin Ma; Lisheng Yu; Jilei Zhang; Shangwei Ji; Yuanyuan Jing (BMJ Open)
Objective We aimed to determine the association between meteorological factors and sudden sensorineural hearing loss (SSNHL) audiogram configurations.Design Retrospective review of medical records from 1 October 2007 to 31 December 2018.Setting A tertiary hospital.Participants 510 patients with SSNHL who had data on the exact date of SSNHL onset and underwent audiological evaluation within 14 days were included.Primary and secondary outcome measures Daily values of meteorological factors, including maximum and minimum temperature, mean temperature and its day-to-day change, diurnal temperature range, atmospheric pressure, mean and maximum wind speed and relative humidity, and seasonal distributions.Results Among the 510 patients (259 women (50.8%); mean (SD) age, 46.4 (15.5) years), 108 (21.2%) displayed ascending patterns, 143 (28.0%) displayed descending patterns, 129 (25.3%) displayed flat patterns and 130 (25.5%) displayed profound patterns of audiograms. The diurnal temperature range on the day of SSNHL onset in patients with profound patterns was significantly higher than that in patient with ascending (mean difference (MD), 2.2°C; 95% CI, 0.7°C to 3.7°C; p=0.001) and descending (MD, 1.5°C; 95% CI, 0.1°C to 2.9°C; p=0.031) patterns. The relative humidity was the highest on the day of SSNHL onset in patients with ascending patterns and showed a significant difference compared with that in patients with profound patterns (MD, 8.0%; 95% CI, 0.7% to 15.3%; p=0.026). Seasonal distribution did not differ among patients with different audiogram configurations.Conclusions Profound audiogram patterns correlated with high diurnal temperature range, while ascending audiogram patterns correlated with high relative humidity in patients with SSNHL. No correlation was observed between seasons and audiogram configurations.